Right ventricular remodelling after endo-exclusion during pulmonary valve replacement: evaluation by cardiac magnetic resonance. (20th April 2021) - Lenoir, Marien; Chenu, Caroline; Amrous, Amine; Casalta, Anne-Claire; Guidon, Catherine; Aldebert, Philippe; Macé, Loïc
Abstract: : OBJECTIVES: Pulmonary valve replacement (PVR) performed for pulmonary valve regurgitation is the most common indication for reoperation during mid-to-long-term follow-up after tetralogy of Fallot repair. An aneurysmal dilation of the infundibulum is often associated secondary to the infundibulotomy performed in the first operation. The right ventricular outflow tract reconstruction with endo-exclusion aims to exclude the non-contractile segments of the dilated right ventricular. This study intends to assess the safety and efficiency of the endo-exclusion technique. METHODS: Between January 2010 and December 2018, 86 patients underwent a PVR with ( n = 46) or without ( n = 40) endo-exclusion. The current study compares the outcomes in terms of survival, reintervention, structural valve deterioration, right ventricular function (volume and right ventricular ejection fraction) and pulmonary valve gradient. The median follow-up time was 4.45 years (1.9 months to 9.87 years). RESULTS: There was no 30-day mortality. There was no difference in the freedom from reintervention at 7 years (without endo-exclusion, 97%, versus with endo-exclusion, 94%, log-rank = 0.68) or in the freedom from structural pulmonary valve deterioration at 7 years (without endo-exclusion, 94%, versus with endo-exclusion, 89%, log-rank = 0.94). No significant difference was observed in the indexed right ventricular end-diastolic volume (102.2 ± 34 ml/m 2 in the PVR without endo-exclusion group and 93.3 ± 22 ml/m 2 in the PVR with endo-exclusion group, P = 0.61). No significant difference was observed in the right ventricular function (right ventricular ejection fraction: 46 ± 11% in the PVR without endo-exclusion group and 46 ± 9% in the PVR with endo-exclusion group, P = 0.88). CONCLUSIONS: PVR with or without endo-exclusion is a safe and effective procedure. PVR with endo-exclusion allows implantation without structural deformation of the valve and therefore excellent short- and medium-term results.